Rectal Microbiota Associated With Chlamydia trachomatis and Neisseria gonorrhoeae Infections in Men Having Sex With Other Men - Ceccarani, Camilla; Marangoni, Antonella; Severgnini, Marco; Camboni, Tania; Laghi, Luca; Gaspari, Valeria; D'Antuono, Antonietta; Foschi, Claudio; Re, Maria Carla; Consolandi, Clarissa (Frontiers in Cellular and Infection Microbiology, 2019)
Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) represent the most common agents of sexually transmitted rectal infections among men having sex with other men (MSM). In this study, we assessed the bacterial composition of the rectal microbiota associated with CT and/or NG infections in a cohort of men reporting unsafe rectal intercourse. A total of 125 rectal swabs were collected and four groups were compared: non-infected subjects (n = 53), patients with CT (n = 37), or NG rectal infection (n = 17) and patients with contemporary positivity for CT/NG (n = 18). CT and NG infections were detected by a real-time commercial test and the rectal microbiota composition was analyzed from rectal swabs through sequencing of the hypervariable V3-V4 regions of the 16S rRNA gene. The rectal microbiota of all subgroups was dominated by Prevotellaceae, Enterobacteriaceae, and Ruminococcaceae families. Irrespective of the analyzed subgroup, we found that the rectal environment of all the enrolled MSM was rich in Prevotella and Escherichia genera. Moreover, a shift in the bacterial composition between patients with sexually transmitted rectal infections and controls was noticed: infected patients were characterized by a depletion of Escherichia species, associated with an increase of anaerobic genera, including Peptoniphilus, Peptostreptococcus, and Parvimonas. Overall, the presence of rectal symptoms did not significantly modify the rectal microbiota profiles among the four groups of analyzed patients. We confirmed that HIV-positive patients are characterized by a lower bacterial richness than HIV-negative subjects. However, we found that the presence of HIV has a different impact on bacterial rectal communities compared to CT and NG infections, modifying the relative abundance of several genera, including Gardnerella, Lactobacillus, Corynebacterium, and Sutterella. Information about the rectal microbiota composition in CT and NG infections could shed light on the pathogenesis of these conditions and could contribute to the onset of new strategies for their control.